Enhance photocatalysis performance and mechanism of CdS and Ag synergistic co-catalyst supported on mesoporous g-C3N4 nanosheets under visible-light irradiation. Issue 6 (December 2017) - Arif, Muhammad; Li, Qingyong; Yao, Jiacheng; Huang, Ting; Hua, Yuxiang; Liu, Tianyu; Liu, Xiaoheng
Graphical abstract: Highlights: Hydrothermal construction of ternary heterostructures CdS/Ag/g-C3 N4 nanocomposite catalyst. Enhance visible light driven photocatalysis performance and photostability of CdS/Ag/g-C3 N4 . SSynergistic co-catalytic activity of CdS and Ag under visible light for the degradation of MB and 4-ABA. Enhance visible light absorption of Ag nanoparticles via surface plasmon resonance effect. Abstract: In the present work the photocatalytic activity of CdS(x)/Ag/g-C3 N4 (x = 10, 20, 40, 60 wt% of the CdS) hybrid heterostructured photocatalyst was investigated. Prior the depositions of CdS over the surface of g-C3 N4, an optimal concentration of Ag nanoparticles as electron conducting bridge were deposited between the interfaces of CdS and g-C3 N4 nanosheets. Being as a plasmon metal, the Ag nanoparticles were deposited to increase the absorption of visible light via surface plasmon resonance effect. The deposition of Ag between the interfaces of CdS nanospeheres and g-C3 N4 can greatly facilitate the migration of electron and reduce the electron-hole recombination during the photocatalytic degradation of organic pollutants. The hybrid heterostructure shows significant photocatalytic activity and photostability compare with pure g-C3 N4, CdS and CdS/g-C3 N4 samples. It is concluded that the hybrid heterostructure provide significant photocatalytic degradation activity through an efficient and facilitated electron transfer mechanism.